Genetic Diversity of Bread Wheat Genotypes Grown in Different Landscapes Using SSR Marker Analysis - Babayeva Sevda; Rustamov Khanbala; Abbasov Mehraj (BIO Web of Conferences)
Azerbaijan, a primary gene center, contains a rich diversity of wheat at different altitudes. Studying this diversity is crucial for improving adaptability and resilience to climate change in high altitude regions. A total of 158 bread wheat accessions were analyzed using SSR markers, following CTAB and PCR-based DNA extraction, fragment analysis on an ABI 3130xl Genetic Analyzer and subsequent statistical evaluation. Thirty- five alleles were identified, ranging from 4 to 16 per primer, with an average value of 8.8. The expected heterozygosity (He) ranged from 0.453 to 0.858, with barc212 showing the highest value, while the polymorphism information content (PIC) ranged from 0.392 to 0.846. Var. ferrugineum showed the highest genetic variability, while var. albidum showed the least. The accessions were grouped into three main clusters in the dendrogram. Three accessions from Hajikend (collected from 1258 m) formed distinct clusters with genetic distances ranging from 0.33 to 0.5. Similarly, accessions from Kankendi (700-800 m) showed a genetic distance of 0.67 between clusters. Overall, SSR marker analysis of local bread wheat revealed significant polymorphism, with accessions from high altitude contributing to the diversity. These results provide valuable information for selecting different parental combinations in breeding programs and hybridization efforts, enhancing crop sustainability and food security.